2002
DOI: 10.1186/1471-2407-2-20
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the mechanism of acoustically activated uptake of drugs from Pluronic micelles

Abstract: Background: This paper examines the mechanism of ultrasonic enhanced drug delivery from Pluronic micelles. In previous publications by our group, fluorescently labeled Pluronic was shown to penetrate HL-60 cells with and without the action of ultrasound, while drug uptake was increased with the application of ultrasound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 10 publications
1
51
0
Order By: Relevance
“…The polymer also appears to have a synergistic effect with some chemotherapeutic agents and has been proposed to inhibit the p-glycoprotein that causes multidrug resistance in many cancer cells (114). Pitt et al explored ultrasound as a means to induce drug release of doxorubicin from pluronic micelles (115,119). Even without ultrasound, pluronic has a synergistic effect with the doxorubicin, increasing the toxicity of the chemotherapeutic agent twofold in spite of decreased uptake of the doxorubicin into the cells.…”
Section: Site-specific Drug Releasementioning
confidence: 98%
See 1 more Smart Citation
“…The polymer also appears to have a synergistic effect with some chemotherapeutic agents and has been proposed to inhibit the p-glycoprotein that causes multidrug resistance in many cancer cells (114). Pitt et al explored ultrasound as a means to induce drug release of doxorubicin from pluronic micelles (115,119). Even without ultrasound, pluronic has a synergistic effect with the doxorubicin, increasing the toxicity of the chemotherapeutic agent twofold in spite of decreased uptake of the doxorubicin into the cells.…”
Section: Site-specific Drug Releasementioning
confidence: 98%
“…Ultrasound treatment further increased the toxicity of the drug containing micelles another sixfold (118). In order to explain this, it was proposed that the presence of pluronic unimers aided the toxicity of the drug (119) but the micelles actually sequestered drug away from the cells until ultrasound induced drug release (115,119). The presence of sequestered drug inside the hydrophobic core was determined fluorescently using a doxorubicin analogue, ruboxyl, and it was found that up to 70% of the ruboxyl was sequestered inside of the micelles (118).…”
Section: Site-specific Drug Releasementioning
confidence: 99%
“…Using fluorescent microscopy and flow cytometry, thy also reported that insonation enhanced the intracellular uptake of Pluronic micelles and its internalization into the nucleus of HL60 cells [178][179][180][181][182][183].…”
Section: Micellesmentioning
confidence: 99%
“…Despite the strong dose-dependent antiproliferative effect of antineoplastic drugs on cultured smooth muscle cells, their dosage is restricted in clinical cases because of their side effects. Recently, there have been several reports regarding the enhancement of drug uptake to the tissue by sonoporation [21][22][23][24][25][26]. Ultrasound induces to perturb the cell membrane and/or cell wall to render it more permeable to the drug, and enhances endocytosis or other activated uptake of the entire micelle (with the encapsulated drug) [21].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there have been several reports regarding the enhancement of drug uptake to the tissue by sonoporation [21][22][23][24][25][26]. Ultrasound induces to perturb the cell membrane and/or cell wall to render it more permeable to the drug, and enhances endocytosis or other activated uptake of the entire micelle (with the encapsulated drug) [21]. Doxorubicin is one of the drugs whose uptake is enhanced by sonoporation [21,22].…”
Section: Introductionmentioning
confidence: 99%